Role of Clinical Pharmacists in Optimizing Patient Outcomes: An Updated Review - Al-Otaibi, Waleed Mohammed; Alghamdi, Saleh Mohammed; Alyami, Mansour Rashed; Alotaibi, Mohammed Rasheed; Alhazza, Abdualziz Ibrahim (Journal of Neonatal Surgery, 2025)
Clinical pharmacists play an important role in shaping patient outcomes and helping in the safe and effective use of the patients’ medications. Their role expands beyond the traditional responsibilities of a pharmacist, which involve the dispensing of medication at the community pharmacy. They participate in medication therapy management (MTM), which includes the prevention and management of adverse drug reactions (ADRs), promoting adherence to therapy, educating the patient, and designing individualized medication plans. They are also part of the inter-professional health care team. Clinical pharmacists assist in the identification and resolution of ADRs which are a significant threat to the safety of patients. ADRs are an example of an area where pharmacists can step in to assist patients and avert clinically significant adverse drug reactions. They also aid in understanding the medication prescribed and in the removal of barriers that hinder adherence to the treatment regimen and provide supportive counseling to patients to help them in the adherence to the treatment plan. They work together with physicians, nurses, and other members of the care team to align their medication-related decisions with the patients’ overall care plan in order to prevent medication-related problems and to maximize the positive outcomes of the care plan.